Notes on the Distribution and Natural History of the Eastern Wormsnake (Carphophis amoenus amoenus) in West Virginia - Diefenbacher, Eric H.; Pauley, Thomas K. (Reptiles & Amphibians, 2014)
Small fossorial snakes, such as the Eastern Wormsnake (Carphophis amoenus amoenus), are often neglected in studies since they lead a fossorial life and are frequently hard to find. Since it was last studied nearly 40 years ago, we present an update on distribution, habitat preferences, and diet of the Eastern Wormsnake in West Virginia. We found that this species resides in only a fraction of its original range due to habitat destruction by industrial, residential, and commercial developments. Habitat data suggests this species can tolerate a range of soil temperatures (15–24 °C), air temperatures (23.1 degrees Celsius), and relative humidity (24.5-80%), and can be found on nearly all slope directions. Dietary analysis showed annelids make up the majority of their diet but other invertebrate prey are also taken.